Car restriction policies for better urban health: a low emission zone in Madrid, Spain. - Lebrusán, Irene; Toutouh-el-Alamin, Jamal (Springer Nature, 2020)
The design of most cities prioritizes the use of motorized vehicles, having a negative effect on urban health. A major concern in the European Union (EU) is air pollution, especially nitrogen dioxide (NO2), which causes many inhabitants health problems and decreases the quality of life. A non-expensive way to reduce pollutants is implementing road restriction policies, as the creation of low emission zones. In this work, we analyze the case of Madrid Central, a low emission zone deployed in Madrid, Spain. We evaluate if it was effective to reduce air pollutants and if there were a side effect, as pollution displacement, during its application. Drawing on open data, we analyze air quality at different points of the city, before and during the application of this measure. Taking into account the EU directives in terms of what healthy air means, we consider three metrics: (a) the trend of NO2 concentration in the air in both periods, (b) the difference between the NO2 concentration during both periods, and (c) the percentage of time in which the population is exposed to air with NO2 concentration under a specific threshold (healthy air as defined by the EU). According to the results, Madrid Central significantly reduces the NO2 concentration in the air and does not produce pollution displacement. Thus, the population breathes healthy air during more time, and there is a positive effect on the whole city.
https://openpolicyfinder.jisc.ac.uk/id/publication/16667
Keywords: Aire - Contaminación; Tráfico urbano; Urban Health; Low Emissions Zone; Pedestrianization; Air Pollution